Apakah IPM, Pengangguran, Dan Pendapatan Perempuan Berpengaruh Dalam Menurunkan Kemiskinan di Kota Surabaya? - Salva Aulia Abda; Hendry Cahyono (Universitas Negeri Surabaya, 2022)
This study aims to determine the effect of HDI, unemployment, and the contribution of women's income to poverty in the city of Surabaya. Using quantitative analysis with time series data from 2010-2020 with multiple regression analysis method. The results show that poverty in the city of Surabaya can be explained by the variable HDI, unemployment, and the contribution of women's income by 96.54% (R2). It was found that the HDI variable had a negative and significant effect with a probability value of 0.0008. The open unemployment rate variable has a positive and significant effect with a probability value of 0.0495. While the contribution of women's income has no effect and is not significant with a probability value of 0.1837. Simultaneously, the three variables have a significant and significant effect on poverty with a probability value of 0.000018.